Efficacy and safety of rituximab for membranous nephropathy in adults: a meta-analysis of RCT - Mao, Baike; Han, Jiahui; Wang, Jia; Ye, Kan (Frontiers in Nephrology, 2025)
BackgroundMembranous nephropathy (MGN) represents a significant challenge in nephrology, with Rituximab emerging as a potential therapeutic intervention.MethodsA comprehensive systematic review was conducted using PubMed, EMBASE, and Web of Science databases, focusing exclusively on randomized controlled trials (RCTs) from January 2002 to November 2024. Stringent eligibility criteria were applied, including studies with at least ten participants, with data extracted by two independent reviewers. The meta-analysis utilized fixed and random effects models to assess Rituximab’s efficacy and safety across multiple outcome measures.ResultsThe meta-analysis revealed nuanced findings across different follow-up periods. At 6 months, complete remission rates showed non-significant odds ratios ranging from 2.12 to 2.48. By 12 months, the pooled odds ratio was 0.8085 (95% CI: 0.2238-2.9213), with complete remission rates varying between 13.8% and 19.4%. Notably, at 24 months, the common effects model demonstrated a statistically significant odds ratio of 5.0792 (95% CI: 2.2609-11.4107, p < 0.0001). Proteinuria reduction showed consistent improvement, with a median difference of 4.3225. Adverse event analysis indicated a relatively low risk, with an odds ratio of 0.9706 (95% CI: 0.5781-1.6297).ConclusionRituximab demonstrates potential efficacy in treating MGN, with promising long-term outcomes and a favorable adverse event profile.